Impact of clinical pharmacist collaboration in patients beginning insulin pump therapy: a retrospective and cross-sectional analysis. (23rd April 2013) - Ledford, James L.; Hess, Rick; Johnson, Frank P.
Abstract: Objective: To measure clinical and qualitative outcomes in patients with diabetes mellitus transitioning from intensive insulin therapy using multiple daily injections (MDI) to continuous subcutaneous insulin infusion (CSII) initiated and managed by clinical pharmacists under a collaborative practice agreement in a primary care setting without an endocrinologist. Research design and methods: This study was a retrospective and cross-sectional analysis of data from an electronic medical record (EMR) and patient survey at a large primary care private practice. Patients with type 1 or type 2 diabetes who were ≥18 years old, started on CSII between 2007 and 2010, and had at least one follow-up visit post-CSII were analyzed. Mean HbA1c results were stratified across 3-month intervals post-CSII initiation and compared to pre-CSII levels. Body mass index (BMI), the number of diabetes-related clinic visits with the primary care physician (PCP), and non-insulin diabetes medication use was compared pre- and post-CSII initiation. Paper-based questionnaires were used to assess patient satisfaction with CSII vs MDI and pharmacist-led services. Results: Twenty-five patients were included in the analysis. HbA1c decreased from 8.69 to 7.52% pre and post-CSII, respectively ( p < 0.001). HbA1c also decreased across all 3-month intervals post-CSII. BMI decreased from 33.0 to 32.3 kg/m 2 pre- and post-CSII, respectively ( p = 0.085). Fewer diabetes-related PCP visits were completed post-CSII (5.09 vs 3.78 visits/year, p = 0.009), and less non-insulin diabetes medications were prescribed post-CSII ( p < 0.001). Patients felt more comfortable controlling glycemic excursions and resultant insulin adjustments with CSII compared to MDI ( p < 0.001). Conclusions: Pharmacist-led CSII services appear to improve diabetes control in patients requiring intensive insulin therapy. Patients report greater comfort using CSII and strong confidence in the abilities of the pharmacist. Physician–pharmacist collaboration in the management of intensive insulin therapy in the primary care setting should be further explored.